AI Ethics Implementation In Indonesia Hospitals: Challenges Or Opportunities - Iswara Sanantagraha, Arnastya; Leslie Hendric Spits Warnars, Harco; Prabowo, Harjanto; Sfenrianto, Sfenrianto; Puspitaloka Mahadewi, Erlina (International Journal of Science, Technology & Management, 2025)
In the last five years, the technology adoption in Indonesia has begun to use advances in artificial intelligence (AI) ethics to improve healthcare services. This change has had a significant impact on several institutions, especially the hospital industry. This paper provides an overview of hospital institutions in Indonesia that are implementing AI ethics. AI ethics comprehensive review of 54 papers from the Scopus, PubMed and Google Scholar database was used to develop our methodology. The existing literatures, which includes studies from various disciplines such as education, healthcare, information communication technology (ICT), licensing, law, hospitality, and economic services, demonstrated the widespread implementation of AI in these fields. We have found potentiality benefit of AI implementation in Indonesian hospital which focusing on increasing patient outcomes and also equalizing of healthcare service. This output can be done with find out the strategy to maximizing its benefit and paralely to decrease and minimizing the rise of ethic risk. This review concludes that AI implementation in Indonesian Hospital come with significantly opportunity for increasing patient healthcare outcome and equality of healthcare services. We provide a new view for organizing governance research, that identifies gaps in the existing literature speciality in healthcare and suggests future directions, for research utilizing technology in AI ethics.